Feline Obesity in Veterinary Medicine: Insights from a Thematic Analysis of Communication in Practice - Phillips, Alexandra M.; Coe, Jason B.; Rock, Melanie J.; Adams, Cindy L. (Frontiers in Veterinary Science, 2017)
Feline obesity has become a common disease and important animal welfare issue. Little is known about how, or how often, veterinarians and feline-owning clients are addressing obesity during clinical appointments. The purpose of this qualitative study was to characterize verbal and non-verbal communication between veterinarians and clients regarding feline obesity. The sample consisted of video-recordings of 17 veterinarians during 284 actual appointments in companion animal patients in Eastern Ontario. This audio-visual dataset served to identify 123 feline appointments. Of these, only 25 appointments were identified in which 12 veterinarians and their clients spoke about feline obesity. Thematic analysis of the videos and transcripts revealed inconsistencies in the depth of address of feline obesity and its prevention by participating veterinarians. In particular, in-depth nutritional history taking and clear recommendations of management rarely took place. Veterinarians appeared to attempt to strengthen the veterinary-client relationship and cope with ambiguity in their role managing obesity with humor and by speaking directly to their animal patients. Clients also appeared to use humor to deal with discomfort surrounding the topic. Our findings have implications for communication skills training within veterinary curricula and professional development amongst practicing veterinarians. As obesity is complex and potentially sensitive subject matter, we suggest a need for veterinarians to have further intentionality and training towards in-depth nutritional history gathering and information sharing while navigating obesity management discussions to more completely address client perspective and patient needs.